A computational-efficient active sound tuning system for steady-state and transient vehicle powertrain response. (1st January 2014) - Duan, Jie; Li, Mingfeng; Lim, Teik C.
Conventional vehicle active noise control (ANC) methods aimed mainly at attenuating the cabin interior noise usually do not account for sound quality effects. In this paper, an active sound tuning (AST) system is proposed to reshape the vehicle powertrain response based on the predetermined vehicle interior sound quality criteria. Since it is important to develop a computational-efficient algorithm in real-world application, the time-frequency domain filtered-x least mean square (TF-FXLMS) algorithm is utilised in the AST system. The proposed TF-FXLMS algorithm significantly reduces the computational complexity compared to the conventional time-domain FXLMS algorithm by calculating the gradient estimate in frequency domain. The proposed AST system applied to powertrain response is validated by tuning individual engine order response, which is targeted for either enhancement or attenuation, under both steady-state and transient operating conditions.